Robert Gildea, Fighters in the Shadows: A New History of the French Resistance - Voglis, Polymeris (Historein, 2019)
Review of Robert Gildea, Fighters in the Shadows: A New History of the French Resistance. London: Faber and Faber, 2015. 593 pp.